Pengaruh Beban Kerja, Lingkungan Kerja dan Budaya Organisasi Terhadap Kepuasan Kerja Karyawan - Inayat Hanum Indriati; Natalia Ratna Ningrum; Martina Ratri Wulandari (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2026)
This study aims to analyze 1) the effect of workload on job satisfaction; 2) the effect of work environment on job satisfaction; 3) the effect of organizational culture on job satisfaction; 4) the effect of workload, work environment, and organizational culture on job satisfaction together. The study period started from January to June 2025 on employees of the production department of PT Surya Beton Precast Magelang. This type of research includes quantitative research using a sample of 54 employees and sample determination using saturated samples. Interviews and questionnaires were used to collect data. The measurement instrument used a Likert scale with five answer choices. Multiple linear regression analysis was used to answer the hypothesis through the SPSS 27.0 for windows program, consisting of t-test, F-test and coefficient of determination. The results of the analysis show that partially workload has a negative and significant effect on job satisfaction as evidenced by the regression coefficient of -0.419 and sig 0.001 <0.05. The work environment has a positive and significant effect on job satisfaction as indicated by the regression coefficient of 0.437 and sig 0.001 <0.05. Organizational culture has a positive and significant effect on job satisfaction, as indicated by the regression coefficient of 0.434 and sig 0.001 <0.05. The results of simultaneous testing show that workload, work environment, and organizational culture significantly influence job satisfaction, as evidenced by the F value of 184,560 and sig 0.001 <0.05. The contribution of the workload, work environment, and organizational culture variables is shown by the Adjusted R Square value of 0.912, the remaining 0.088 is determined by other factors outside this research model.